Efektivitas Metode Circuit Learning dalam Meningkatkan Keaktifan Belajar Siswa dalam Mata Pelajaran Qur’an Hadist - Partono (Al-Ishlah: Jurnal Pendidikan Islam, 2020)
Abstract This study aims to determine how the efforts of a teacher in increasing the activity of student learning in the Qur'anic lessons of Hadith through the circuit learning method. In this paper also provides a way to use the circuit learning method in learning the Qur'an hadith. By using this method it is hoped that it can influence the activeness of students in the learning process and ends in an increased understanding of the Qur'anic lessons of Hadith. Circuit learning model is one of the strategies used in the implementation of the learning process through a group approach by requiring students to develop words in their own language related to material that has been studied as a group. This research took place at MA Sultan Agung Bloar. The results of this study note that the circuit learning method is effective in increasing student learning activeness seen from students' participation in answering and giving comments in learning using their own language.